Engagement as co‐constructing knowledge: A moral necessity in public health research. (17th May 2019) - Pratt, Bridget
Abstract: Undertaking engagement in public health research is ethically essential. There is a growing emphasis on practicing engagement as the co‐construction of knowledge, which goes beyond other common forms of engagement in health research practice: consulting and informing. Taking such an approach means researchers jointly construct knowledge with research users and beneficiaries; all parties design and conduct research together and share decision‐making power. This article makes the normative argument that such engagement is necessary to achieve the foundational moral aims of public health research—building relations of equality and addressing the health needs of those considered disadvantaged—which reflect the field's underlying commitment to social justice. It next identifies and discusses three ways in which co‐constructing knowledge advances those moral aims: by facilitating self‐determination, supporting individuals' right to research, and maximizing social knowledge to address cognitive and epistemic injustice. Objections to the arguments presented in the article are then articulated and defended against.